Growth of Penicillium chrysogenum in palm oil mill effluent concentrate - Mohamed Salleh Suwandi (Serdang, Selangor (Malaysia), 2013)
The filamentous fungus Penicillium chrysogenum is tested for its ability to grow on the palm oil mill effluent concentrate prepared by the process of ultra-filtration of the filtrate after the removal of the coarse suspended matter. The fungus was found to grow well on the concentrate and biomass yields in the range of 12-16 gl(*-l) were obtained when the carbon to added nitrogen ratio in the growth media was 15:1 and 20:1 respectively